The code breaker Jennifer Doudna, gene editing, and the future of the human race - Walter Isaacson (New York Simon & Schuster, 2021)
When Jennifer Doudna was in sixth grade, she came home one day to find that her dad had left a paperback titled The Double Helix on her bed. She put it aside, thinking it was one of those detective tales she loved. When she read it on a rainy Saturday, she discovered she was right, in a way. As she sped through the pages, she became enthralled by the intense drama behind the competition to discover the code of life. Even though her high school counselor told her girls didn?t become scientists, she decided she would.
Includes bibliographical references and index.
Keywords: Gene editing